Pengaruh Penerapan Kurikulum Merdeka Belajar Terhadap Prestasi Akademik: Studi Kasus Mahasiswa PBA UIN Mataram - Fahmi, Izul; Suparmanto, Suparmanto; Swala, Meta; Walid, Muhammad; Hadi Anggara, Wiryan (Al-Wazan: Journal of Arabic Education, 2024)
The curriculum is a crucial element in the implementation of learning in a school. The curriculum plays a role in determining the direction, purpose, or goals of national education. Without a curriculum, any education system will not be well-executed, and educational goals cannot be optimally achieved. So important is the curriculum to education that the government has made amendments to it ten times. Since 2020 until now, the Ministry of Education and Culture has issued a policy in the form of a curriculum change from the 2013 curriculum to the "Merdeka Belajar" curriculum. The main purpose of these curriculum amendments is to maximize and optimize students' learning outcomes or academic achievements at all levels, from elementary, junior high, senior high/vocational schools, to higher education. This is done by giving students the freedom to choose subjects according to their talents and interests. In light of this, the researcher is interested in conducting a study on the impact of the "Merdeka Belajar" curriculum on students' learning outcomes, to determine whether this curriculum change has a positive or negative effect on students' academic achievements. In this research, the researcher uses a quantitative approach with a correlational analysis method. Data collection instruments include questionnaire completion and data retrieval in the form of the GPA of third-semester students. The researcher's analysis of the questionnaire results and GPA data indicates that the "Merdeka Belajar" curriculum (MBKM) has a significant and positive influence on students' learning outcomes or academic achievements.